Combining the Fibrinogen/Albumin Ratio and Systemic Inflammation Response Index Predicts Survival in Resectable Gastric Cancer - Junbin Zhang; Yongfeng Ding; Weibin Wang; Yimin Lu; Haiyong Wang; Haohao Wang; Lisong Teng (Gastroenterology Research and Practice)
Aims. Predicting the prognosis of gastric cancer using tumour-node-metastasis (TNM) staging is difficult as patients with the same TNM stage exhibit different prognoses. Methods. This study investigated the prognostic value of the preoperative fibrinogen/albumin ratio (FAR)-systemic inflammation response index (SIRI) score in resectable gastric cancer (rGC). Results. Clinicopathological features of 231 rGC patients were analysed retrospectively. Patients were divided into three groups: FAR-SIRI score 2 (FAR≥0.071 and SIRI≥0.84), 1 (FAR<0.071 and SIRI≥0.84), and 0 (SIRI<0.84). Higher FAR-SIRI scores were associated with larger tumours, poorer differentiation, and advanced TNM stage (P<0.05). Compared to those with FAR-SIRI scores of 0, patients with scores of 2 had poorer overall survival (OS). The FAR-SIRI score was an independent prognostic factor for OS in rGC. Conclusion. The present data demonstrated that FAR-SIRI scores predicted radical gastric cancer surgical outcomes and may serve as a blood marker for identifying high-risk patients.